Antagonismo de Purpureocillium sp. (cepa UdeA0106) con hongos aislados de cultivos de flores (2014)
ABSTRACT: Studies developed in the BIOMA research group of the Universidad de Antioquia showed how the fungus Purpureocillium sp. (Idea0106) may biocontrol a plague known as symphylans (subphylum Myriapodas: class Symphyla). The goal of this study was to identify fungal genera isolated from different substrates (symphylans and soils) and determine their antagonistic capacity, as well a collection of biocontrol strains, over Purpureocillium sp. (Idea0106). Nine fungal strains were isolated from symphylans samples, belonging to 3 genera, and 17 strains were isolated from soil samples, belonging to 10 genre. The antagonism tests consisted of an in vitro test using the dual culture technique in Petri dishes using sabouraud dextrosa agar (SDA) culture medium, with was conducted on 16 strains: 12 obtained from the isolates and 4 from the collection of the BIOMA research group. The variables evaluated were the growth radius in the confrontations and the percentage of radial growth inhibition (PICR) at 7 and 14 days. Data were analyzed using generalized linear mixed model using the SAS Proc GLIMMIX procedure in an independent manner. The fungus Purpureocillium sp. (Idea0106) was inhibited by Vollutella sp (Vo.UdeA0109), Paecilomyces sp. Isolate 2 (Pa.UdeA0109) and Peyronella sp. (Pe. Idea 0108) (p <0,001), while the results of the strains Beaveria sp. (BeUdeA0109) Dendrodochium sp. (De UdeA0109), Myrothecium sp. (Mi. UdeA0109), Paecilomyces sp. isolated 1 (Pa. UdeA0309), Paecilomyces sp. isolated 3 (Pa.UdeA0209), Lecanicillium sp (Le.UdeA0109), and Purpureocillium sp. (Hy.UdeA0109) were not significant. The analyses showed that interactions with undesirable results may occur between fungal strains when conducting control activities.